2016
DOI: 10.3126/jucms.v3i2.14283
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Psychiatric Referral From Emergency Department of a Tertiary Level Hospital in Nepal

Abstract: INTRODUCTION: Emergency department serves as one of the gateway through which patients with psychiatric disorders come for treatment. The referral to the psychiatry department enables a psychiatrist to provide services to these patients in need. So, the study of this pathway of care becomes important. MATERIAL AND METHODS: A total of 100 consecutive patients referred from emergency to the department of psychiatry were enrolled in this study. Their socio-demographic variables, reason and purpose for referral wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…23 In our study AUD was the most common diagnosis seen in 22% of subjects. AUD is common disorder referred for assessment to a psychiatrist from ICU 15 , emergency department 24 and from other departments. 25 Substance use disorders including alcohol are one of the common disorders that need psychiatry evaluation and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…23 In our study AUD was the most common diagnosis seen in 22% of subjects. AUD is common disorder referred for assessment to a psychiatrist from ICU 15 , emergency department 24 and from other departments. 25 Substance use disorders including alcohol are one of the common disorders that need psychiatry evaluation and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that among all psychiatric referrals in emergency settings, a call for the assessment of suspected dissociative disorder is the most common. [ 7 ] The tendency of dissociative disorders to emulate physical disorders makes assessment especially tricky. A wide range of medical conditions could mimic symptoms of dissociative disorders, medical conditions may produce and/or exacerbate psychiatric symptoms in patients already suffering from a mental illness, patients with pre-existing medical conditions can develop psychiatric symptoms and occasionally medical conditions and dissociative disorders can arise together.…”
Section: Assessmentmentioning
confidence: 99%
“…[8] There are many recent works on emergency psychiatry presentations which state that schizophrenia, substance use disorders, mania, and dissociative symptoms are the common presenting illnesses at the emergency department, rather than the somatoform disorder. [9][10][11][12] These recent works on psychiatric emergency clearly state a presentation and profile of the psychiatric emergency patients, which differ largely from the profile stated in the article by Naskar et al [1] The description of "Distribution of the various reasons for referral from various departments," in Naskar et al, [1] states that 22.38% of patients referred by other departments had a previous psychiatric illness. [1] It would have been more informative if the authors had provided the reason for referral to the psychiatrist, as there is a possibility that the readers may misinterpret that these patients would have been sent for just repeating the prescriptions of psychotropics since they are in the hospital for other medical illnesses.…”
Section: Comments On "Utilization Of Emergency Psychiatrymentioning
confidence: 99%
“…[8] There are many recent works on emergency psychiatry presentations which state that schizophrenia, substance use disorders, mania, and dissociative symptoms are the common presenting illnesses at the emergency department, rather than the somatoform disorder. [9101112] These recent works on psychiatric emergency clearly state a presentation and profile of the psychiatric emergency patients, which differ largely from the profile stated in the article by Naskar et al [1]…”
mentioning
confidence: 96%